2010
DOI: 10.1007/s11882-010-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Histamine H4 Receptor in Atopic Dermatitis

Abstract: The pathology of atopic dermatitis is orchestrated on the cellular level by several different cell types in the characteristic skin lesions. In such lesions, histamine as a mediator of many biological functions is also present in high concentrations. Most of the cells involved in the inflammatory responses express the histamine H1 and H2 receptors, but drugs targeting these receptors are not clinically effective. The discovery of the fourth histamine receptor, which is differentially expressed on immune and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Recent evidence, however, has challenged the initial paradigm that the blockade of the H 4 receptor is related to inhibition of inflammation, because some pharmacological discrepancies have emerged: H 4 receptor activation, rather than blockade, was found to display anti‐inflammatory effects in some experimental models (19,24–26) and, on the other hand, the ‘standard’ H 4 receptor antagonist JNJ7777120 (5,27) was found to behave as an agonist in some settings (25,26,28) or to be ineffective on ear swelling in mouse dermatitis models, despite reducing the scratching behaviour (29,30). Finally, it was recently shown that the preventive administration of H 4 receptor antagonists has no impact on the development of acute skin lesions in a canine atopic dermatitis model (31).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence, however, has challenged the initial paradigm that the blockade of the H 4 receptor is related to inhibition of inflammation, because some pharmacological discrepancies have emerged: H 4 receptor activation, rather than blockade, was found to display anti‐inflammatory effects in some experimental models (19,24–26) and, on the other hand, the ‘standard’ H 4 receptor antagonist JNJ7777120 (5,27) was found to behave as an agonist in some settings (25,26,28) or to be ineffective on ear swelling in mouse dermatitis models, despite reducing the scratching behaviour (29,30). Finally, it was recently shown that the preventive administration of H 4 receptor antagonists has no impact on the development of acute skin lesions in a canine atopic dermatitis model (31).…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, histamine has been the most well-known pruritogen. Histamine was found at high concentrations in AD lesions and most of the cells involved in the inflammatory responses express the histamine 1 receptor (H1R) and histamine 2 receptor (H2R)(Mommert et al , 2011). There is a specific chemosensitive subpopulation of C-fibers that mediate histamine-induced pruritus (Schmelz, 2001; Schmelz et al , 2003).…”
Section: Specific Features Of Pruritus In Atopic Dermatitismentioning
confidence: 99%
“…Histamine, for which four receptors (H1R, H2R, H3R and H4R) have been identified, is probably the best studied of these mediators. The fact that in most countries, H1-antihistamines are purchased over the counter without prescription as the most frequent form of self-medication for allergic diseases (50) contrasts with the disappointing clinical efficacy observed for drugs targeting H1R and H2R (48,51,52). In this regard, the fourth histamine receptor H4R gained much attention as a potential novel drug target, because this receptor appears to be involved in the pathogenesis and perpetuation of allergic inflammation and pruritus, as well as genetic dysregulation of H4R expression on immune and nonimmune cells in atopic dermatitis (52,53).…”
Section: Pruritus: More Than Just Histaminementioning
confidence: 99%
“…The fact that in most countries, H1-antihistamines are purchased over the counter without prescription as the most frequent form of self-medication for allergic diseases (50) contrasts with the disappointing clinical efficacy observed for drugs targeting H1R and H2R (48,51,52). In this regard, the fourth histamine receptor H4R gained much attention as a potential novel drug target, because this receptor appears to be involved in the pathogenesis and perpetuation of allergic inflammation and pruritus, as well as genetic dysregulation of H4R expression on immune and nonimmune cells in atopic dermatitis (52,53). Recently, in an animal model of chronic allergic contact dermatitis induced by repeated epicutaneous challenge using 2,4,6-trinitro-1-chlorobenzene (TNCB), the H4R receptor was shown to be implicated in the exacerbation of skin lesions, recruitment of mast cells and eosinophils, promotion of a Th2 cytokine profile and an increase in serum IgE (54).…”
Section: Pruritus: More Than Just Histaminementioning
confidence: 99%